Multi-moving Loads Induced Vibration of FG Sandwich Beams Resting on Pasternak Elastic Foundation - Wachirawit Songsuwan; Monsak Pimsarn; Nuttawit Wattanasakulpong (Walailak Journal of Science and Technology (WJST), 2021)
The dynamic behavior of functionally graded (FG) sandwich beams resting on the Pasternak elastic foundation under an arbitrary number of harmonic moving loads is presented by using Timoshenko beam theory, including the significant effects of shear deformation and rotary inertia. The equation of motion governing the dynamic response of the beams is derived from Lagrange’s equations. The Ritz and Newmark methods are implemented to solve the equation of motion for obtaining free and forced vibration results of the beams with different boundary conditions. The influences of several parametric studies such as layer thickness ratio, boundary condition, spring constants, length to height ratio, velocity, excitation frequency, phase angle, etc., on the dynamic response of the beams are examined and discussed in detail. According to the present investigation, it is revealed that with an increase of the velocity of the moving loads, the dynamic deflection initially increases with fluctuations and then drops considerably after reaching the peak value at the critical velocity. Moreover, the distance between the loads is also one of the important parameters that affect the beams’ deflection results under a number of moving loads.
Keywords: Composite Structure Analysis and Optimization; Vibration and Dynamic Analysis; Structural Engineering and Vibration Analysis